Discovery of A Novel Palladium Catalyst for the Preparation of Enynes with a Copper- and Ligand-Free Sonogashira Reaction - Mi, Xia; Huang, Mengmeng; Feng, Yujian; Wu, Yangjie (Synlett, 2012)
A new palladium(II) complex based on N,N-dimethylethanolamine, (SP-4-1′)-bis[N,N-dimethylaminoethoxy-kN,O]palladium(II) which coordinates with two moles of AcOH, has been synthesized. The structure of the complex has been established by X-ray diffraction analysis. Using this complex as a catalyst, a series of conjugated enynes were successfully synthesized by Sonogashira cross-coupling reaction in the absence of co-catalyst CuX and any ligand at room temperature during 20 hours affording the corresponding products in moderate to excellent yields. The optimized catalytic systems are tolerant in the presence of a broad variety of functional groups in the substrates. The catalytic system was found to be ineffective for vinyl chloride. Moreover, it was found that (Z)-β-bromostyrene reacts with terminal alkynes with retention of the steric configuration and the transformation of most of the Z-isomer did not occur in this reaction.
Keywords: N,N-dimethylethanolamine; copper-free; ligand-free; Sonogashira reaction; enyne; β-bromostyrene; stereochemistry